Comparison of Staphylococcus aureus Genotypes Recovered from Cases of Bovine, Ovine, and Caprine Mastitis - Mørk, T. (American Society for Microbiology (ASM), 2005)
Staphylococcus aureus is an important pathogen in domestic ruminants. The main objective of this study was to determine the similarity of epidemiologically unrelated S. aureus isolates from bovine, ovine, and caprine mastitis. By pulsed-field gel electrophoresis, 160 different pulsotypes (PTs) were identified among 905 isolates recovered from 588 herds in 12 counties in Norway. Based on estimates of similarity, using an 80% cluster cutoff, the isolates were assigned to 47 clusters. One cluster included 62% of all the isolates and more than 45% of the isolates from each host species. Twenty-three PTs included isolates from more than one host species; these 23 PTs represented 72% of all the isolates. The six most prevalent PTs included isolates from all host species and contained 45% of the bovine isolates, 54% of the ovine isolates, and 37% of the caprine isolates. Antimicrobial susceptibility testing of 373 of the isolates revealed resistance to penicillin in 2.9% and to streptomycin in 2.4%; only 1.9% were resistant to 1 of the other 11 antimicrobials tested. The results of this study suggest that a small number of closely related genotypes are responsible for a great proportion of S. aureus mastitis cases in cows, ewes, and goats in Norway and that these genotypes exhibit little or no host preference among these species. Selection due to antimicrobial resistance appears not to have contributed to the predominance of these genotypes.